2019
DOI: 10.1177/1687814019827144
|View full text |Cite
|
Sign up to set email alerts
|

Research on the pressurization performance of an impeller in a multi-phase pump under different working conditions

Abstract: In order to improve the working performance of the impeller in a multi-phase pump under different working conditions and expand the range of the high-efficiency areas of the multi-phase pump, each section of the impeller was divided into an inlet section, middle section and outlet section. The pressurization performance of different areas within the impeller was obtained by numerical calculation under different flow rates and different gas volume fractions, respectively. The results show that the pressurizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Due to the great difference in physical properties between gases and liquids, those two phases separate when pumping a gas-liquid mixture with a rotodynamic multiphase pump. Differing from the liquid phase regarding pressure, the gas phase is likely to accumulate on the impeller hub and blade suction surface [4,5], which reduces the work capacity of the impeller, increases the energy loss, and leads to a rise in pressure, causing the efficiency of the multiphase pump to not meet the requirements of engineering practices [6,7]. In addition, the pressure pulsation in the multiphase pump surges when the gas volume fraction in the pump reaches a certain level, affecting the stable operation of the multiphase pump [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the great difference in physical properties between gases and liquids, those two phases separate when pumping a gas-liquid mixture with a rotodynamic multiphase pump. Differing from the liquid phase regarding pressure, the gas phase is likely to accumulate on the impeller hub and blade suction surface [4,5], which reduces the work capacity of the impeller, increases the energy loss, and leads to a rise in pressure, causing the efficiency of the multiphase pump to not meet the requirements of engineering practices [6,7]. In addition, the pressure pulsation in the multiphase pump surges when the gas volume fraction in the pump reaches a certain level, affecting the stable operation of the multiphase pump [8].…”
Section: Introductionmentioning
confidence: 99%
“…Shi GT. et al [2] employed the numerical simulation approaches to prob into the pressurization performance in different impeller regions under the different flow rates and IGVFs. Results demonstrated that the closer to the shroud, the stronger the pressurization performance at the front of blades was; however, at the latter half of blades, the shorter distance to the hub, the more strength of the pressurization performance would be.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above studies, many other scholars have analyzed and discussed the pump in terms of design method [22,23], energy conversion characteristics [24,25], interphase force [26][27][28] and clearance flow [29,30]. In general, for the pump many scholars in many aspects have done a lot of research work and achieved good results, but for the pump in the gas-liquid two-phase flow there is not sufficient research.…”
Section: Introductionmentioning
confidence: 99%